Reservoir Sensitivity Analysis of Tight Sandstone and Its Controlling Factors: A Case Study from Chang 4+5 to Chang 6 Reservoirs in N 212 Well Block of Nanniwan Oilfield, Ordos Basin - Pingtian Fan; Yuetian Liu; Ping Li; Yanqin Guo; Weichu Yu; Baiqiang Li (Geofluids)
Reservoir sensitivity can lead to the physical or chemical reactions to block the pore throat. It is helpful for reducing the damage on tight sandstone reservoir to study the reservoir sensitivity and its controlling factors. This paper mainly focuses on the tight sandstone of the Chang 4+5 and Chang 6 reservoirs of the Yanchang Formation in the Nanniwan Oilfield, Ordos Basin. The reservoir sensitivity characteristics were evaluated through the core sensitivity experiment after the petrological and petrophysical analysis and pore structure study. The influencing factors on tight sandstone reservoir sensitivity were discussed from several aspects, such as clay mineral composition, porosity, permeability, and pore structure. The results show that the rock type of the Chang 4+5 and Chang 6 reservoirs in the N 212 well block of the Nanniwan Oilfield is mainly arkose, with the mean porosity of 11.2% and 8.45% and the mean permeability of 0.35×10−3 μm2 and 0.44×10−3 μm2, respectively. The clay mineral components mainly include chlorite and illite/smectite. Both the two reservoirs are characterized by moderate to weak velocity sensitivity, moderate to weak water sensitivity, moderate to strong salt sensitivity, weak acid sensitivity, and moderate to weak alkali sensitivity. In specific, the Chang 4+5 reservoir is stronger in velocity and salt sensitivities, while it is weaker in water, acid, and alkali sensitivities than those of the Chang 6. The major controlling factors on reservoir sensitivity are clay mineral component, petrophysical property, and pore structure. Among these, the velocity sensitivity displays the positive correlation with pore structure, porosity, and permeability. The water sensitivity will become strong with the increase of the volume content of illite/smectite, but weak with the getting better of pore structure. The acid sensitivity is positively correlated with the volume content of chlorite but is negatively correlated with pore structure. With the getting better of pore structure, the salt sensitivity and alkali sensitivity will become strong and weak, respectively. The research results can be as the guidance for the tight sandstone reservoir protection in the study area and the adjustment and optimization of the regional reservoir development scheme.